Patogenicidade de Alternaria spp. na videira 'Niágara Rosada' e severidade de míldio em 'BRS Vitória' - Pereira, Carolina Bertuzzi (2015)
The leaf blight is an important disease in cultivating Niágara Rosada (Vitis labrusca) in the region of Jales, São Paulo, for causing early defoliation of the plants, damaging the development and maturation of fruits and branches. Although it has been found since the end of the nineties, the etiology of leaf blight of grapevine remains not elucidated, with only reports of its association with fungi of the genus Alternaria. In the first part of this study, we investigated the pathogenicity of Alternaria isolates on grapevine leaves. Pathogenicity tests were performed in young plants of 'Niagara Rosada'. were inoculated by spraying a spore suspension in sterile water or in water/oil emulsion, as well as by depositing plugs of mycelium on the surface of leaves. The plants were kept in a humid chamber for different periods and then in greenhouse. It is also investigated the induction of leaf blight symptoms of by successive applications of copper hydroxide and paraquat applications to accelerate endophytic colonization. The species identification was based on morphological characteristics and DNA analysis of a portion of Alt a1 gene, which is considered informative about Alternaria phylogeny. It was found that successive applications of copper hydroxide can cause chlorosis and necrosis on leaves, having some resemblance with the symptoms of leaf blight. In addition, Alternaria spp. were found colonizing healthy leaves, evidencing their endophytism. Seven isolates were identified as A. resedae (= A. septorioides) and two isolated as A. alternata. In the second part of the study, damages of downy mildew (Plasmopara viticola) were assessed in the new seedless table grape cultivar BRS Vitória in comparison with the traditional table grape cultivar Benitaka (from Italy group, Vitis vinifera) in northern Paraná. It was observed that the cultivar BRS Vitória is less damaged by downy mildew than the cultivar Benitaka.